Analogue modelling an array of the FitzHugh–Nagumo oscillators - Tamaševičiūtė, Elena; Mykolaitis, Gytis (Nonlinear Analysis: Modelling and Control, 2012)
The purpose of the paper is to show that analogue electronic modelling is an extremely fast technique compared to conventional digital computing, especially when solving large sets of coupled nonlinear differential equations. An array of thirty FitzHugh–Nagumo type electronic oscillators, modelling dynamics of the brain neurons, is considered. The decrease of time consumption by a factor of several thousands is demonstrated. The work delivers a perspective of how to implement convenient analogue models of complex dynamical networks.
Keywords: analogue modelling; ordinary differential equations